Analisis Prediksi Tingkat Kebangkrutan Perusahaan Dengan Metode Altman Z-Score Dan Springate (Studi Kasus Pada Perusahaan Sub Sektor Pertambangan Minyak dan Gas Bumi yang Tercatat di Bursa Efek Indonesia Pada Tahun 2009-2012) - Tri Utama Putra; Arlin Ferlina MochT (Trunojoyo University of Madura, 2014)
This research aimed to predict bankruptcy using the Altman Z-Score and Springate on mining companies sub-sector oil and gas companies listed on the Stock Exchange 2009-2012. One of the things behind the decline in revenues caused by the company's oil and gas industry. And a decline in oil production from year to year. By using quantitative descriptive method, the population in this study is a sub-company financial statements of oil and gas mining. The type of sample used is purposive sampling to obtain a sample of five companies, namely Prabu Energi Tbk (ARTI), Benakat Petroleum Energy Tbk (BIPI), Elnusa Tbk (ELSA), Energi Mega Persada Tbk (ENRG), dan Radiant Utama Interinsco Tbk (RUIS). The results showed the company's bankruptcy prediction mining and oil and gas sub-sector model with Altman Z-Score, for ARTI 2009 in the category of distress zone, in the following years in the category of gray zone. BIPI always get into the safe category. ELSA in 2009 and 2010 are in the category of a safe zone, and in the next two years are in the gray zone category. For each year the ENRG always fall into the category distress zone. Ruis 2009 in the category of safe zone, 2010 in the category of gray zone, and the following year in the category distress zone. Prediction of corporate bankruptcy in mining and oil and gas sub-sector with Springate models, which enter into the healthy category, namely ELSA company in 2009 and Ruis company in 2009 and 2010. Additionally, all companies would be predicted to fall into the category of bankruptcy because bankruptcy.